Electrochemical machining of a solid-state sintered ceramic – A parameter study. (November 2017) - Schneider, M.; Safonow, E.; Junker, N.; Schubert, N.; Michaelis, A.
Abstract: The present work deals with the electrochemical machining (ECM) of a commercially produced solid-state sintered silicon carbide ceramic (EKasic®D). Current controlled pulse experiments under near-ECM conditions are carried out using a micro-electrochemical flow cell. The influence of different pulse-on time and pulse amplitude, respectively, on the efficiency, the removal rate and the surface morphology was studied. The results clearly show that the higher the applied current density and the longer the pulse-on time the higher the removed material volume. Again, the current efficiency is limited at approximately 25%. Supplementary, electrolyte variations regarding concentration and temperature show a small influence on the efficiency. Highlights: A solid-state SiC ceramic is successfully machined by ECM. The higher the applied current density the higher the removal rate. The higher the applied current the thinner the remaining oxide film. The current efficiency amounts to approximately 25%.